2020
DOI: 10.3390/coatings10030212
|View full text |Cite
|
Sign up to set email alerts
|

The Structure, Morphology, and Mechanical Properties of Ta-Hf-C Coatings Deposited by Pulsed Direct Current Reactive Magnetron Sputtering

Abstract: Ta, Hf, TaCx, HfCx, and TaxHf1-xCy coatings were deposited by reactive pulsed Direct Current (DC) magnetron sputtering of Ta or Hf pure metallic targets in Ar plus CH4 gas mixtures. The properties have been investigated as a function of the carbon content, which is tuned via the CH4 flow rate. The discharge was characterized by means of Optical Emission Spectroscopy and, in our conditions, both Ta-C and Hf-C systems seem to be weakly reactive. The structure of the as-deposited pure tantalum film is metastable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Through the first-principles calculations, Kim et al [27] found that overall elastic properties and overall metal abundance of Ta x Hf 1−x C increased with increasing the TaC content; thus, the mechanical properties did not improve monotonically. This result was subsequently confirmed by some research [28][29][30]. However, the failure mechanism of C f /Ta x Hf 1−x C-SiC composites is not clear, especially the effect of the composition and applied load on the mechanical behavior, which needs an in-depth study.…”
Section: Introductionmentioning
confidence: 56%
“…Through the first-principles calculations, Kim et al [27] found that overall elastic properties and overall metal abundance of Ta x Hf 1−x C increased with increasing the TaC content; thus, the mechanical properties did not improve monotonically. This result was subsequently confirmed by some research [28][29][30]. However, the failure mechanism of C f /Ta x Hf 1−x C-SiC composites is not clear, especially the effect of the composition and applied load on the mechanical behavior, which needs an in-depth study.…”
Section: Introductionmentioning
confidence: 56%
“…It is crucially important that usually the synthesis of refractory carbides of transition metals (including high-entropy carbides) is performed in vacuum using various sintering techniques, like spark plasma sintering (SPS). [6,8,10,14,15,17,18] Less common synthesis methods include hot isostatic pressing, [15] and other techniques, [19][20][21][22] but all mentioned techniques require vacuum for the synthesis of high-quality carbide materials and thus are expensive and resource-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…The attractive thing is that ternary Ta-Hf-C solid solution ceramics formed by TaC and HfC have been proven to have the higher hardness (~30 GPa) and the highest melting point temperature (>4200 K) from experimental and computational studies, which has been incorporated into the surface engineering wear-resistant material [3][4][5]. Many methods have been developed for the synthesis of Ta-Hf-C solid solution coatings, including plasma spraying, chemical vapor deposition, and physical vapor deposition [6,7]. Based on copolyfocal magnetron sputtering, Yate et al [8] first realized the deposition of Ta-Hf-C film on stainless steel substrate.…”
Section: Introductionmentioning
confidence: 99%